The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.2220/biomedres.33.111
|View full text |Cite
|
Sign up to set email alerts
|

Gymnopilin-a substance produced by the hallucinogenic mushroom, Gymnopilus junonius-mobilizes intracellular Ca2+ in dorsal root ganglion cells

Abstract: Gymnopilus junonius is a widely spread mushroom in Japan and well known as a hallucinogenic mushroom. Gymnopilin was purified from the fruiting body of G. junonius and was reported to act on the spinal cord and depolarize motoneurons. This is the only evidence that gymnopilin has a biological effect on animals and no mechanism of the action has been determined at all. In this study, we examined effects of gymnopilin on intracellular Ca . These results indicate that gymnopilin activated phospholipase C and mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…We have recently reported that gymnopilins activate two intracellular signal cascades including the phospholipase C-dependent one (Miyazaki et al, 2012) and the cAMP-dependent one (Nishio et al, 2012). In addition, here we report that gymnopilins act on the nAChR.…”
Section: Junoniussupporting
confidence: 65%
See 2 more Smart Citations
“…We have recently reported that gymnopilins activate two intracellular signal cascades including the phospholipase C-dependent one (Miyazaki et al, 2012) and the cAMP-dependent one (Nishio et al, 2012). In addition, here we report that gymnopilins act on the nAChR.…”
Section: Junoniussupporting
confidence: 65%
“…Gymnopilins were purified from the wild fruiting body of G. junonius collected in Japan according to the procedure reported previously (Aoyagi et al, 1983;Miyazaki et al, 2012). In brief, wild fruiting bodies of G. junonius were lyophilized, crunched and stored at -20 ºC.…”
Section: Isolation and Purification Of Gymnopilinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we reported that gymnopilins activated Gq-coupled GPCRs expressed in neurons and glial cells in dorsal root ganglia and cerebral cortex. 7) Gymnopilins may be distributed into the central nervous system crossing the blood brain barrier and may act directly on cells in the central nervous system to excite the vasomotor center. Underlying mechanisms including this possibility need to be examined in the future study.…”
Section: Fig 4 Effects Of Sq-22536 On the Vasodilating Effect Of Gymentioning
confidence: 99%
“…Recently, we reported that gymnopilins act on mammalian neurons and glial cells. 7) Gymnopilins are likely to bind to some G protein-coupled receptor and mobilize cytosolic Ca 2+ from the intracellular Ca 2+ store. When fruiting bodies of G. junonius are ingested, gymnopilins are absorbed in the gastrointestinal tract and carried into the blood.…”
mentioning
confidence: 99%